The Use of Case Study and Grounded Theory Research Strategy in Interpretive Research in Tourism - Risfandini, Andini; Adinda Putri Mustika (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2023)
The purpose of this paper is to discuss case studies and grounded theory research strategies in the field of tourism to encourage researchers to adopt the qualitative approach in conducting research. This paper addresses the topic of how to improve the reliability, validity, and generalizability of qualitative research. Yin (2018) proposed that a case study can be used as a research strategy in qualitative research to verify and extend a theory, meanwhile, for Eisenhardt (1989) and Gioia et al. (2012), a case study is used to build a theory using grounded theory. Both strategies are equally useful in the tourism sector. The choice of the research strategy depends on the research paradigm and how the researchers position themselves in the paradigm inquiry namely: ontologically, epistemologically, and methodologically. This article is significant to encourage researchers in tourism to adopt a qualitative approach in conducting research when the researchers intend to gain a deep understanding of the phenomena in tourism such as customer behavior, purchase intention, decision-making process, and tourist motivation.